Antioxidant Effect on Oxidation Stability of Blend Fish Oil Biodiesel with Vegetable Oil Biodiesel and Petroleum Diesel Fuel - M. Hossain; S.M.A Sujan; M.S. Jamal (Center of Biomass & Renewable Energy (CBIORE), 2013)
Two different phenolic synthetic antioxidants were used to improve the oxidation stability of fish oil biodiesel blends with vegetable oil biodiesel and petroleum diesel. Butylhydroxytoluene (BHT) most effective for improvement of the oxidation stability of petro diesel, whereas tert butylhydroquinone (TBHQ) showed good performance in fish oil biodiesel. Fish oil/Rapeseed oil biodiesel mixed showed some acceptable results in higher concentration of antioxidants. TBHQ showed better oxidation stability than BHT in B100 composition. In fish oil biodiesel/diesel mixed fuel, BHT was more effective antioxidant than TBHQ to increase oxidation stability because BHT is more soluble than TBHQ. The stability behavior of biodiesel/diesel blends with the employment of the modified Rancimat method (EN 15751). The performance of antioxidants was evaluated for treating fish oil biodiesel/Rapeseed oil biodiesel for B100, and blends with two type diesel fuel (deep sulfurization diesel and automotive ultra-low sulfur or zero sulfur diesels). The examined blends were in proportions of 5, 10, 15, and 20% by volume of fish oil biodiesel.